Digital off-axis holography with angular multiplexing and synthetic aperture - Wang, Zhaomin (2018)
This paper discusses conventional synthetic-aperture method combined angular multiplexing in digital holography to increase the resolution and to enlarge the field of view at the same time. A structured illumination is used to realize angular multiplexing. A camera is moved by a motorized x-y stage, and scanning is performed at imaging plane. In this way we extend the band-pass for single hologram recording as well as obtain a greater sensor area resulting in a larger numerical aperture (NA). A larger NA enables a more detailed reconstruction combined with a smaller depth of field. Moreover, a phase map of the object is experimentally presented.